Oversight Hearing on Safe School Study. Hearing before the Subcommittee on Economic Opportunity of the Committee on Education and Labor. House of Representatives, Ninety-Fifth Congress, Second Session - Congress of the U.S., Washington, DC. House Committee on Education and Labor; Congress of the U.S., Washington, DC. House Committee on Education and Labor ([Washington, D.C.]] : Distributed by ERIC Clearinghouse, 1978)
This document consists of transcripts of a hearing held by the Subcommittee on Economic Opportunity of the Committee on Education and Labor of the House of Representatives, on the subject of crime in the schools. Intended as a follow-up to the publication by the National Institute of Education (NIE) of "Violent Schools--Safe Schools: The Safe School Study," the hearings were focused by subcommittee chairman Ike Andrews on the question of what the federal government could do to improve the situation in the schools. In addition to the hearing transcripts, this document contains prepared statements by those testifying, and supporting materials including letters, portions of the NIE report, and reprints of other related publications. (PGD)
ERIC Note: Not available in paper copy due to small print of original document; Many pages may be illegible; For related documents, see ED 149 464-466.
Educational level discussed: Elementary Secondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Administrator Role; Delinquency; Elementary Secondary Education; Federal Government; Government Role; Hearings; School Security; Violence; Legal/Legislative/Regulatory Materials